ACCLIMATIZATION FEATURES OF BULL-CALVES DANISH BLACK- MOTLEY BREED - Зюбіна, О. В.; Щербатюк, Н. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
It is know that at present, the process of moving cattle among the various zones of the country and from abroad. Quite sensitive to changes in the environment are young organisms, which growth and development, determining the relevance of research. The aim of research was to study the productive qualities – weight gain, body structure measurements and exchange gas energetic bull-calves Danish black-motley breed. To achieve this goal, in similar circumstances, breeding farm NVK "Ridnyi krai" Khmelnitsky region the principle of analogues formed two groups of calves: I - Ukrainian black-motley of a lactic breed, II - Danish black-motley.For 18 months growing average daily Danish black-motley bulls were 3% more domestic counterparts. Data analysis linear growth of the body structure characterizes good development and harmony of body shapes sufficient Danish black-motley breed. Body weight Indicators, increases indicate insignificant difference from the Ukrainian black-motley of a lactic bulls, indicating the excellent features of acclimatization in Ukraine imported animals